Transportation, State Marketing, and the Taxation of the Agricultural Hinterland - Gersovitz, Mark (Journal of Political Economy, 1989)
In raising revenues, governments of poor countries affect farm gate prices for export crops. Because agriculture is dispersed, interventions have spatial effects, leading to an integrated analysis of taxation, marketing, and transportation. Policies to be used singly or together include land, export, and transportation taxes/subsidies and variants of state marketing, in which only government procures crops. An export tax and a transport subsidy may be optimal. With state marketing, important aspects of buying depots are numbers, locations, spatial pattern of prices paid, and movement of output toward or away from the ultimate market. These policies also affect transport investment strategies.